Nematodes from galls on Myrtaceae. VI. Fergusobia from galls on Angophora in Australia, with description of F. colbrani n. sp. and key - Davies, Kerrie A.; Taylor, Gary S.; Nelson, Leigh A.; Yeates, David; Giblin-Davis, Robin M. (Zootaxa, 2014)
Collection data and biological information is presented on the Fergusobia (Nematoda: Neotylenchidae)/ Fergusonina (Diptera: Fergusoninidae) mutualism inducing galls on Angophora in Australia. Three species and two morphospecies have been recognised. Fergusobia colbrani Davies n. sp. is described from soft spheroid leaf galls on Angophora floribunda. It is characterised by a combination of morphological characters including a small C-shaped parthenogenetic female with a short broadly conoid tail, an arcuate infective female with an almost hemispherical tail tip, and an arcuate to barely J-shaped male with an angular spicule having a notched tip and mid-length leptoderan bursa. A key to the species and morphospecies of nematodes collected from Angophora is presented. Possible relationships of these organisms are discussed based on evidence from the nematode morphology, gall forms, and the morphology of the dorsal shield of the associated Fergusonina fly larvae.